Sobrevivência e produtividade de minicepas de Eucalyptus benthamii cultivadas em hidroponia na presença de BAP - Prates, Gisele de Fátima (2014)
This work aimed to evaluate BAP effect in survival and productivity of E. benthamii ministumps samplings handled in hydorponics system. For clonal mini-garden formation handled in hydroponic system, it was used grafted clones of E. benthamii with 100 days. The plants were cultivated in planters with nutrient solution. The experiment was conducted in a randomized bloks design with five treatments, four repetitions and ten plants in each experimental unit at the first trial, and six plants at the second one. The treatments were consisted of four dosages of BAP and the control. In the first trial, with 105 days, the highest mean values of ministumps survival (80%), and increased production of shoots (25) were recorded to control. In the second trial, the ministumps presented low survival rate. The average survival on the six evaluations were: 63, 45, 65, 64 and 58, respectively, for the treatments 1, 2, 3, 4 and 5. Three samples were collected, and the best performance were recorded by the control treatment, with an average yield of 20.25; 14.75 and 8 ministumps, respectively, for first, second and third sample.